DRILL WEAR DURING THE BORING OF PARTICLE BOARD: A MULTI-FACTOR ANALYSIS INCLUDING EFFECTS OF MINERAL CONTAMINANTS - Boleslaw Porankiewicz; Grzegorz Wieloch (BioResources, 2008)
This paper evaluates and discusses multifactor non-linear, statistical dependencies of drill side-edges recession VBK and drill diameter recession DW on the cutting path length LC, the content of hard mineral contaminants CMC, the size of contaminant particles SMC, and the Mohs hardness MH. Significant influence of the cutting path LC, the content CMC of hard mineral contaminants (HMC), and the size of contaminant particles SMC was found, whereas the Mohs hardness MH of the contamination particles was less important.